Malignant Catarrhal Fever in Indonesia and Its Control Strategy - Rini Damayanti (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2016)
Malignant catarrhal fever (MCF) is an immunoproliferative and lethal disease of many species of the order Artiodactyla (such as families Bovidae, Cervidae and Suidae) caused by a member of the MCF virus (MCFV) group belongs to the genus Macavirus in the subfamily Gammaherpesvirinae. There are two types of MCF i.e. Wildebeest-Associated MCF (WA-MCF) which is caused by Alcelaphine Herpesvirus-1 (AlHV-1) with wildebeest as reservoir animal; and Sheep-Associated MCF (SA-MCF) which is caused by Ovine herpesvirus 2 (OvHV-2) with sheep and goats as reservoir animals. AlHV-1 virus has already been isolated whereas OvHV-2 has not been isolated so that vaccines are not yet available. Both types cannot be differentiated by clinical and pathological findings. This disease was previously diagnosed based on the epidemiological information and clinicopathological findings, but now it can be diagnosed by using molecular biological tests. This paper describes the epidemiology of MCF virus, MCF cases in Indonesia and efforts to control this disease. In Indonesia, SA-MCF cases have been reported almost in all provinces as endemic as well as epidemic nature. Separation of reservoir animal with susceptible species, "producing" a SA-MCF virus free sheep and attempt to develop a recombinant vaccine against SA-MCF is the main control strategy that can be suggested.